On the tip of my tongue - Warr, Tracey (Journal of Writing in Creative Practice, 2013)
Abstract A discursive account and photo-essay covering the author’s participation in Writing Practice: A Celebration of Writing Pad at Arnolfini, Bristol and Translating: Paired Practice in London, 2012, and the author’s own writing on contemporary artists and text-based teaching with Fine Art students.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qd2NwLjYuMS4xMDdfMQ